Secondary Cratering From Rheasilvia as the Possible Origin of Vesta's Equatorial Troughs. Issue 3 (24th March 2023) - Hirata, Naoyuki
Abstract: Asteroid 4 Vesta has a set of parallel troughs aligned with its equator. Although previous evaluations suggest that it is of shock fracturing tectonic origin, we propose that the equatorial troughs can be created by secondary cratering from the largest impact basin, Rheasilvia. We calculated the trajectories of ejecta particles from Rheasilvia by considering Vesta's rapid rotation. As a result, we found that secondary craters should be parallel to the latitude. In particular, if we assume that ejecta particles are launched at an initial launch velocity of approximately 350–380 m/s and a launch angle of 25°, the parallel equatorial troughs, the Divalia Fossae, can be suitably explained by secondary cratering. This model works well on objects, such as Haumea, Salacia, and Chariklo, but not on Mercury, the Moon, and regular satellites. Plain Language Summary: Asteroid 4 Vesta has a set of parallel troughs aligned with its equator. We propose that the equatorial troughs can be created by secondary cratering from Rheasilvia, the largest impact basin of Vesta. We calculated the trajectories of ejecta particles from Rheasilvia by considering Vesta's rapid rotation. As a result, we found that secondary craters should be parallel to the latitude. In particular, the pattern of troughs indicates that ejecta particles were launched at an initial launch velocity of approximately 350–380 m/s and a launch angle of 25°. Key Points: We propose a new mechanism for the formation of equatorial troughs on Vesta We calculated the distribution of ejecta particles launched from Rheasilvia We found that secondary cratering from Rheasilvia matches with the equatorial troughs